Primerjalna analiza spodbujanje ustvarjalnosti in inovativnosti v izbranih organizacijah - Krajnc, Bojan (Revija za univerzalno odličnost, 2024)
Research question (RQ): How to carry out an evaluation of the component of promoting creativity and innovation based on the excellence model of the European Foundation for Quality Management (hereinafter EFQM) in the selected company? Purpose: The purpose of the research was to assess the level of development of the building blocks for promoting creativity and innovation, and based on the obtained results, formulate proposals for improvements. Method: In the theoretical part of the research, we focused on a descriptive approach, with the help of which we reviewed the professional literature and available empirical research. In the empirical part of the research, we basically performed a qualitative research method. In order to obtain primary data, we conducted a structured interview with five managers in all organizational units of the selected company. We performed basic and more demanding statistical processing on the information obtained in this way.
Keywords: EFQM; gradniki in podgradniki; izbrana organizacija; kakovost; menedžment; ustvarjalnost in inovativnost